CHARACTERISTIC FEATURES AND ACTUAL PROBLEMS OF DEVELOPMENT OF RURAL AREAS OF RA (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
Due to the diversity of natural complex and focal nature urbanization, rural areas of RA stand out with characteristic lines and have an essential role in the development of regions. In the article, based on the generalization of factual data the features of RA rural areas are presented, and actual problems of rural settlements as elements of rural areas are revealed.
Keywords: rural areas; rural population; rural settlements; dynamics of population and settlements; development problems